Investigating the Source of Student Self-Efficacy and its Relations to Affective Factors in Mathematics Learning - Amien, Sulthon; Abidin, Ratno; Hidayatullah, Achmad; Muhammad , Ridlwan (Revija za elementarno izobraževanje, 2023)
The purpose of this study was to explore the source of students’ self-efficacy and its relation to motivation, attitude, and students’ perception of teacher support in mathematics learning. Three hundred and fifty participants were selected using a stratified random sampling method. The study was survey-based and quantitative; data were analysed through statistical tests. Findings showed that most students reported having good grades in math. The source of self-efficacy in mathematics significantly correlates with attitude, intrinsic motivation, and students’ perception of teacher support.
Keywords: self-efficacy, attitude, student motivation, teacher support